Alfvén Mach number and IMF clock angle dependencies of sunward flow channels in the magnetosphere. Issue 7 (11th April 2013) - Eriksson, S.; Rastätter, L.
<x xml:space="preserve">Abstract</x> [1] Interplanetary coronal mass ejections associated with strong interplanetary magnetic field (IMF) By have been shown to enhance the neutral density in low Earth orbit. The enhancement has been linked to strong downward Poynting fluxes embedded within ionospheric channels of significant sunward ExB drift (2000–3000 m/s). Here we present MHD results describing the magnetospheric counterpart of the ionospheric flow channel that Defense Meteorological Satellite Program (DMSP) encountered on 15 May 2005. It is shown that the clock angle of maximum sunward flow (θFC) depends on the IMF clock angle θFC = α * θIMF − 1.3° with α = (0.30, 0.38, 0.43, 0.45) at X = (4, 2, 0, −2) RE. This is poleward of the magnetic null point region. The flow also depends on the solar wind Alfvén Mach number Vx = Vx0 − δv * MA. The critical MA = Vx0 / δV for Vx = 0 decreases from MA = 3.42 (X = 4 RE) to MA = 2.40 (X = −2 RE). The low MA and θIMF conditions that characterized the X = 2 RE flow and resulted in strong Poynting flux occurred for 16% of all 167 h in 1998–2008 with Dst < −180 nT.